Indoxacarb poisoning causing methemoglobinemia treated with parenteral vitamin C: a case report - Lokesh Koumar Sivanandam; H. Arunkumar; Pranay Marlecha; Varsha Madamanchi; Chanchal Maheshwari; Mohammed Quader Naseer; Vivek Sanker; Tirth Dave (Journal of Medical Case Reports, 2024)
Abstract Introduction This case study reports on a suicide attempt involving indoxacarb and vitamin C. Indoxacarb is a neurotoxic insecticide used in agriculture and as a flea controller in pets. Cotton, vegetables, and fruits are treated with indoxacarb, an insecticide that can be applied both indoors and outdoors. It causes skin allergies, methemoglobinemia, and hemolytic anemia. It is also attributed to allergic reactions through ingestion, inhalation, physical contact, and translaminar action. This case report highlights use of vitamin C in methemoglobinemia caused by indoxacarb poisoning. Indoxacarb poisoning has the potential to be extremely serious and even lethal. In this instance, the patient initially had no symptoms after ingesting a substance containing indoxacarb in an attempt at suicide. However, further tests revealed methemoglobinemia and low oxygen levels. Case presentation A 28-year-old south-east Asian female patient ingested an insecticide containing 5.25% novaluron, 4.5% indoxacarb, and 25% thiamethoxam, and reported that she noticed muddy brown urine but presented with no active signs or symptoms of poisoning. Upon examination, the patient was fully conscious, alert, and hemodynamically stable, but had an oxygen saturation of 84%. Gastric lavage was performed, and blood investigations revealed a muddy-brown-colored blood sample and methemoglobin levels of 12%. The patient was treated with high-dose vitamin C and showed significant improvement, with a drop in methemoglobin levels to 1.2% and an increase in oxygen saturation to 97%. Discussion Indoxacarb poisoning can cause severe methemoglobinemia. Vitamin C may be a useful treatment option for methemoglobinemia caused by indoxacarb, particularly in cases in which traditional treatment with methylene blue is contraindicated or not tolerated. Hence high doses of ascorbic acid, that is, vitamin C, were administered to the patient, which lowered their methemoglobin levels and improved oxygen levels without much safety concerns. Conclusion This example emphasizes the significance of early indoxacarb poisoning detection and treatment as well as the possible advantages of utilizing ascorbic acid in the management of methemoglobinemia, and highlights the use of vitamin C in the treatment of methemoglobinemia caused by indoxacarb poisoning. Therefore, it is important for healthcare professionals to be aware of the potential for indoxacarb to cause methemoglobinemia and to consider vitamin C as a treatment option.